The Analysis Of The Effect Of Firm Characteristics On The Completeness Of Public Company’s Voluntary Disclosure - Adiutrix Maria Irayanti Seran (CV. ULIL ALBAB CORP, 2022)
The purpose of this study is to analyze the influence of firm characteristics and voluntary disclosure levels in the annual reports of listed companies in Indonesia Stock Exchange. The degree of voluntary disclosure is calculated by an index which is based on background information, non-financial statistic, projected information, and management discussion and analysis. This study using 434 companies in 2021 as a sample and applies the multiple regression analysis. The finding of this study shows that firm characteristics; profitability, firm size, liquidity and industry type have significant relationship with voluntary disclosure, while leverage, age and ownership have no significant with voluntary disclosure. This study can be very helpful for the shareholders, creditors and financial management in making decision about giving voluntary disclosure in annual reports as it provides adequate information for decision making.